(adsbygoogle = window.adsbygoogle || []).push({}); 1. The problem statement, all variables and given/known data

[tex]\int\frac{x^2}{\sqrt{x^2+4}}dx[/tex]

2. Relevant equations

n/a

3. The attempt at a solution

Letting [tex]x=2tan\theta[/tex] and [tex]dx=2sec^2\theta d\theta[/tex]

[tex]\int\frac{x^2}{\sqrt{x^2+4}}dx=\int\frac{4tan^2\theta}{\sqrt{4+4tan^2\theta}}2sec^2\theta d\theta=\int\frac{8tan^2\theta sec^2\theta}{\sqrt{4(1+tan^2\theta)}}d\theta=4\int\frac{tan^2\theta sec^2\theta}{sec\theta}d\theta=[/tex][tex]4\int tan^2\theta sec\theta d\theta=4\int(sec^2\theta -1)sec\theta d\theta=4\int (sec^3\theta-sec\theta)d\theta=[/tex][tex]4\int sec^3\theta d\theta-4\int sec\theta d\theta=-4\int\frac{cos\theta}{cos^2\theta}d\theta+4\int\frac{cos\theta}{cos^4\theta}d\theta= [/tex][tex]-4\int\frac{cos\theta}{1-sin^2\theta}d\theta+4\int\frac{cos\theta}{(cos^2\theta)^2}d\theta=-4\int\frac{cos\theta}{1-sin^2\theta}d\theta+4\int\frac{cos\theta}{(1-sin^2\theta)^2}d\theta[/tex]

now letting [tex]u=sin\theta[/tex]and[tex]du=cos\theta d\theta[/tex][tex]-4\int\frac{1}{1-u^2}du+4\int\frac{1}{(1-u^2)^2}du=-4\int\frac{1}{(1-u)(1+u)}du+4\int\frac{1}{(1-u^2)^2}du[/tex]

using partial fraction decomposition I get

[tex]\frac{1}{(1-u)(1+u)}=\frac{A}{1-u}+\frac{B}{1+u}[/tex] multipying both sides by [tex]1-u^2[/tex][tex]1=A(1+u)+B(1-u)[/tex] Letting u=1 we get that [tex]A=\frac{1}{2}[/tex] now letting u=-1 we get that [tex]B=\frac{1}{2}[/tex] Then [tex]\frac{1}{(1-u)(1+u)}=\frac{1}{2(1-u)}+\frac{1}{2(1+u)}[/tex]

and [tex]-4\int\frac{1}{(1-u)(1+u)}du[/tex] becomes [tex]-4\int\frac{1}{2}(\frac{1}{1-u}+\frac{1}{1+u})du=-2(\ln\mid1+u\mid-\ln\mid1-u\mid+c[/tex]note that [tex]u=sin\theta=\frac{x}{\sqrt{x^2+4}}[/tex][tex]-2(\ln\mid1+\frac{x}{\sqrt{x^2+4}}\mid-\ln\mid1-\frac{x}{\sqrt{x^2+4}}\mid)+c=-2\ln\mid1+\frac{x}{\sqrt{x^2+4}}\mid+2\ln\mid1-\frac{x}{\sqrt{x^2+4}}\mid+c=\ln\mid(1-\frac{x}{\sqrt{x^2+4}})^2\mid-\ln\mid(1+\frac{x}{\sqrt{x^2+4}})^{2}\mid+c=\ln\mid\frac{(1-\frac{x}{\sqrt{x^2+4}})^2}{(1+\frac{x}{\sqrt{x^2+4}})^2}\mid+c[/tex]

and our original integral becomes [tex]\ln\mid\frac{(1-\frac{x}{\sqrt{x^2+4}})^2}{(1+\frac{x}{\sqrt{x^2+4}})^2}\mid+4\int\frac{1}{(1-u^2)^2}du[/tex]

now this is where I am stuck because I can't seem to figue out partial fraction decomposition on [tex]\frac{1}{(1-u^2)^2}=\frac{A}{(1-u^2)}+\frac{B}{(1-u^2)^2}[/tex] multiplying through I get that [tex]1=A(1-u^2)+B[/tex]

Letting u=1 B=1 then[tex]1=A(1-u^2)+1[/tex] then for any u A=0 and I am left with [tex]\frac{1}{(1-u^2)^2}=0+\frac{1}{(1-u^2)^2}[/tex] and I still can't integrate.

Please don't just say I am not using the correct partial fraction method because I have searched and searched but can't find a method on this type of fraction.

**Physics Forums | Science Articles, Homework Help, Discussion**

Dismiss Notice

Join Physics Forums Today!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Homework Help: Stuck on this integral (using partial fraction decomposition)

Have something to add?

Draft saved
Draft deleted

**Physics Forums | Science Articles, Homework Help, Discussion**